(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
A world problem of increasing importance is the continuous increase of greenhouse gases and the accompanying global warming. Growing global industries, excessive use of fossil fuels, along with deforestation and agriculture, which are major greenhouse gas polluters, are cited as the main causes. Of the greenhouse gases with the largest share, but also the possibility of control is CO2. This gas is vital for the growth and development of plants and, through them, is included in the continuous carbon cycle. On this basis, strategies for sustainable development in agriculture are built since this is one of the main sectors contributing to the increase in carbon emissions. The present study tracked the seasonal dynamic of CO2 uptake by natural grasslands positioned at two altitudes by measuring photosynthesis and plant and soil respiration. A significant variation in CO2 uptake capacity was observed depending on the climatic conditions.